2007
DOI: 10.1200/jco.2007.11.9453
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Centrally Reviewed Expression of Estrogen and Progesterone Receptors in a Randomized Trial Comparing Letrozole and Tamoxifen Adjuvant Therapy for Postmenopausal Early Breast Cancer: BIG 1-98

Abstract: Central review changed the assessment of receptor status in a substantial proportion of patients, and should be performed whenever possible in similar trials. PgR expression did not affect the relative efficacy of letrozole over tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
289
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(307 citation statements)
references
References 24 publications
6
289
3
9
Order By: Relevance
“…ER ϩ PR Ϫ tumors show greater genomic instability and twice as many DNA copy number gains or losses as compared with ER ϩ PR ϩ and ER Ϫ PR Ϫ tumors [9]. They showed copy number gains within regions 11q13 (68 -72 Mb), 12q14-q15 (63-68 Mb), and 17q21-q25 (45-73 Mb), and copy number losses within regions 11q13-q25 (82-134 Mb) and chromosome 22 [10].…”
Section: Characteristics Of Er ؉ Pr ؊ Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…ER ϩ PR Ϫ tumors show greater genomic instability and twice as many DNA copy number gains or losses as compared with ER ϩ PR ϩ and ER Ϫ PR Ϫ tumors [9]. They showed copy number gains within regions 11q13 (68 -72 Mb), 12q14-q15 (63-68 Mb), and 17q21-q25 (45-73 Mb), and copy number losses within regions 11q13-q25 (82-134 Mb) and chromosome 22 [10].…”
Section: Characteristics Of Er ؉ Pr ؊ Breast Cancermentioning
confidence: 99%
“…These tumors are a mixture of three different molecular subtypes [9]: (a) a ϩ/Ϫ tumor associating with a ϩ/ϩ tumor by gene signature, (b) a ϩ/Ϫ tumor associating with a Ϫ/Ϫ tumor by gene signature, and (c) a ϩ/Ϫ tumor not aligned with either a ϩ/ϩ tumor or a Ϫ/Ϫ tumor by gene signature (true ER ϩ PR Ϫ ) (Fig. 5).…”
Section: Characteristics Of Er ؉ Pr ؊ Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Among postmenopausal women, earlier studies have shown a significant trend in reduction of recurrence rate with higher ER levels among tamoxifen treated, supporting the significance of stronger ER content in endocrine treatment [5][6][7][8].…”
Section: Discussionmentioning
confidence: 92%
“…Remaining research questions include the benefit of LHRH agonists, in addition to tamoxifen, and if LHRH agonists have a role among those not achieving amenorrhea during cytotoxic chemotherapy. Moreover, efficacy of endocrine treament in relation to estrogen receptor (ER) status is mainly established among postmenopausal women, and the different endocrine milieu in premenopausal women may affect the predictive ability of ER status [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%